Analysis of 75 Candidate SNPs Associated With Acute Rejection in Kidney Transplant Recipients: Validation of rs2910164 in MicroRNA MIR146A. Issue 8 (August 2019) - Oetting, William S.; Schladt, David P.; Dorr, Casey R.; Wu, Baolin; Guan, Weihua; Remmel, Rory P.; Iklé, David; Mannon, Roslyn B.; Matas, Arthur J.; Israni, Ajay K.; Jacobson, Pamala A.
Abstract : Background: Identifying kidney allograft recipients who are predisposed to acute rejection (AR) could allow for optimization of clinical treatment to avoid rejection and prolong graft survival. It has been hypothesized that a part of this predisposition is caused by the inheritance of specific genetic variants. There are many publications reporting a statistically significant association between a genetic variant, usually in the form of a single-nucleotide polymorphism (SNP), and AR. However, there are additional publications reporting a lack of this association when a different cohort of recipients is analyzed for the same single-nucleotide polymorphism. Methods: In this report, we attempted to validate 75 common genetic variants, which have been previously reported to be associated with AR, using a large kidney allograft recipient cohort of 2390 European Americans and 482 African Americans. Results: Of those variants tested, only 1 variant, rs2910164, which alters the expression of the microRNA MIR146A, was found to exhibit a significant association within the African American cohort. Suggestive variants were found in the genes CTLA and TLR4 . Conclusions: Our results show that most variants previously reported to be associated with AR were not validated in our cohort. This shows the importance of validation when reporting the associations with complex clinical outcomes such as AR. Additional work will need to be done to understand the role of MIR146A in the risk of AR in kidney allograft recipients. Abstract : Supplemental Digital Content is available in the text.